2013
DOI: 10.5194/acp-13-7825-2013
|View full text |Cite
|
Sign up to set email alerts
|

A one-year comprehensive chemical characterisation of fine aerosol (PM<sub>2.5</sub>) at urban, suburban and rural background sites in the region of Paris (France)

Abstract: Abstract. Studies describing the chemical composition of fine aerosol (PM2.5) in urban areas are often conducted for a few weeks only and at one sole site, giving thus a narrow view of their temporal and spatial characteristics. This paper presents a one-year (11 September 2009–10 September 2010) survey of the daily chemical composition of PM2.5 in the region of Paris, which is the second most populated "Larger Urban Zone" in Europe. Five sampling sites representative of suburban (SUB), urban (URB), northeast … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 80 publications
7
103
0
Order By: Relevance
“…Although the literature suggests that a higher OC to OM conversion factor of 2.1 is suitable for rural sites (Bressi et al, 2013;Turpin and Lim, 2001), we still used a uniform value of 1.6 for the sake of spatial comparisons. Therefore, Christoforou et al, 2000).…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature suggests that a higher OC to OM conversion factor of 2.1 is suitable for rural sites (Bressi et al, 2013;Turpin and Lim, 2001), we still used a uniform value of 1.6 for the sake of spatial comparisons. Therefore, Christoforou et al, 2000).…”
Section: Chemical Analysismentioning
confidence: 99%
“…The PM mass and its chemical compositions are governed by chemical processes, the evolution of emission sources, and meteorological conditions (Bressi et al, 2013;, which usually exhibit seasonality. The seasonal patterns of PM 2.5 at the urban sites were mainly driven by OM, SNA, and mineral dust, which were the major components of PM 2.5 during each season.…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…More details on this instrumentation and its comparability with other real-time aerosol analysers can be found in Zorn et al (2008); Sciare et al (2011);Healy et al (2013); Crippa et al (2013); Bressi et al (2013). Basic and acidic annular denuders (3-channel, URG Corp., USA) were mounted upstream of the PILS instrument and downstream of a PM10 inlet having a 50 % cut-off diameter of 10 µm at 16.67 LPM.…”
Section: Atmospheric Station and Instrumental Set-upmentioning
confidence: 99%
“…PMA concentration was calculated using these data and the following formula (Brewer, 1975): (Cl), with a time resolution of 30 min. The chemical composition of non-refractory submicron aerosol has been continuously monitored using a Quadrupole Aerosol Chemical Speciation Monitor (Aerodyne Research Inc.), which has been described in detail by Ng et al (2011).…”
Section: Atmospheric Station and Instrumental Set-upmentioning
confidence: 99%
“…Meanwhile, it is reported that climate change and synoptic circulation (Miao et al, 2017;Ye et al, 2016;Zhang et al, 2012;Zheng et al, 2015a) are of great importance in the transport of pollutants as well. Air pollution is essentially a phenomenon of the atmospheric boundary layer (ABL) and is strongly 5 affected by the thermodynamic and dynamic structure of the ABL (Bressi et al, 2013;Gao et al, 2016;Tang et al, 2016).…”
mentioning
confidence: 99%